2000
DOI: 10.4049/jimmunol.165.12.7171
|View full text |Cite
|
Sign up to set email alerts
|

Tat Protein Is an HIV-1-Encoded β-Chemokine Homolog That Promotes Migration and Up-Regulates CCR3 Expression on Human FcεRI+ Cells

Abstract: Human basophils and mast cells express the chemokine receptor CCR3, which binds the chemokines eotaxin and RANTES. HIV-1 Tat protein is a potent chemoattractant for basophils and lung mast cells obtained from healthy individuals seronegative for Abs to HIV-1 and HIV-2. Tat protein induced a rapid and transient Ca2+ influx in basophils and mast cells, analogous to β-chemokines. Tat protein neither induced histamine release from human basophils and mast cells nor increased IL-3-stimulated histamine secretion fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 72 publications
(98 reference statements)
0
60
0
Order By: Relevance
“…Tat is essential for viral replication, transmission and disease progression [1,[4][5][6][7]. In addition, Tat can modulate the expression of cytokines and cellular genes [6][7][8][9][10][11], and chemokine receptors [12][13][14][15], which are responsible for the transmission of macrophageand T-cell-tropic HIV-1 strains, respectively. In addition, the Tat protein also plays key roles in viral pathogenesis and in the pathogenesis of acquired immune deficiency syndrome (AIDS)-associated Kaposi's sarcoma [8,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Tat is essential for viral replication, transmission and disease progression [1,[4][5][6][7]. In addition, Tat can modulate the expression of cytokines and cellular genes [6][7][8][9][10][11], and chemokine receptors [12][13][14][15], which are responsible for the transmission of macrophageand T-cell-tropic HIV-1 strains, respectively. In addition, the Tat protein also plays key roles in viral pathogenesis and in the pathogenesis of acquired immune deficiency syndrome (AIDS)-associated Kaposi's sarcoma [8,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have shown that by interacting with the ␤-chemokine receptor CCR3, the HIV-1 Tat protein is a potent chemoattractant for human basophils and mast cells. Moreover, Tat protein up-regulates the level of CCR3 mRNA and surface expression of CCR3 on human basophils (10). Recent evidence suggests that a population of basophils and/or mast cells in peripheral blood can be infected in vitro by M-tropic strains of HIV-1 (11,12).…”
Section: T He Human Immunodeficiency Viruses Hiv-1 and Hiv-2 Destroy Cd4mentioning
confidence: 99%
“…The magnetically labeled cells were depleted by retaining them on a MACS column in the magnetic field of the MidiMACS (Miltenyi Biotec). Yields ranged from 3 to 10 ϫ 10 6 basophils with purity Ͼ99%, assessed by basophil staining with Alcian blue, and counting in a Spiers-Levy eosinophil counter (26).…”
Section: Purification Of Peripheral Blood Basophilsmentioning
confidence: 99%
“…Several fractions were collected, and fractions with Ͼ20 ϫ 10 6 basophils and a good purity (Ͼ15%) were enriched by discontinuous Percoll gradients. Basophils were further purified to near homogeneity (Ͼ99%) by depleting B cells, monocytes, NK cells, dendritic cells, erythrocytes, platelets, neutrophils, eosinophils and T cells, using a mixture of hapten-conjugated CD3, CD7, CD14, CD15, CD16, CD36, CD45RA, and anti-HLA-DR Abs and MACS MicroBeads coupled to an anti-hapten mAb (26). The magnetically labeled cells were depleted by retaining them on a MACS column in the magnetic field of the MidiMACS (Miltenyi Biotec).…”
Section: Purification Of Peripheral Blood Basophilsmentioning
confidence: 99%